Preparation of Passive Daytime Cooling Fabric with the Synergistic Effect of Radiative Cooling and Evaporative Cooling. Issue 3 (16th October 2021) - Sun, Yilan; Ji, Yating; Javed, Muhammad; Li, Xiaoyan; Fan, Zhuizhui; Wang, Youquan; Cai, Zaisheng; Xu, Bi
Abstract: Passive daytime radiative cooling (PDRC) has attracted intensive attention due to its great potential in reduced energy consumption. However, the practical application for PDRC is greatly affected by geographical location and the intrinsic cooling power. Herein, a composite flexible fabric with the synergistic effect of evaporative cooling and radiative cooling is reported. A porous polymer coating with both a high solar reflectivity (90%) and a high infrared thermal emissivity (83%) is fabricated on the top side of the fabric, which can achieve effective PDRC performance. Meanwhile, hygroscopic salts are loaded on the bottom side of the fabric, which can capture water vapor at night and realize evaporative cooling during the daytime. The temperature reduction of 10.8 °C can be achieved under the direct sunlight irradiation (465 W m −2 ) for the prepared fabric in the outdoor experiment. The combination of radiative cooling and evaporative cooling breaks through the traditional single passive cooling mode and has great potential in further improving the performance of passive cooling. Abstract : A flexible fabric combining radiative cooling with evaporative cooling is reported toward achieving passive daytime cooling. A temperature reduction of 10.8 °C can be achieved under the direct sunlight irradiation (465 W m −2 ) for the prepared fabric in the outdoor experiment. This passive cooling fabric shows great potential in improving passive cooling performance and prolonging cooling time.